Long-term Trends in the Transition to the Labour Market in Germany - Steffen Hillmert (Intergenerational Justice Review)
Successful transitions from school to work are decisive for success later in life. The situation of young people at this stage is therefore an issue not only for scientific research, but also for public discussion. A high level of institutionalised coordination has traditionally been a core element of the German institutional system, not least with regard to education, training and employment, and this has been associated with comparatively smooth transition patterns. Discussion in recent years has, however, increasingly focused on the problems occurring at these transitions. When assessing this situation, it is not only important to know how many people finally make successful transitions, but also how extended and complex transitions are. Against this background, this paper asks whether and to what extent there has been a de-structuring of the transition to the labour market in Germany – and, linked with it, of the transition to adulthood – as it has been proposed by theories of individualisation. Possible indicators of such a de-structuring would be a de-standardisation of transition patterns, a decreasing social differentiation and a declining significance of school-to-work transitions for other domains of life.